Identifying LPG Usage Inequality and Its Determinants in Eastern Indonesia - Fajritia, Rahajeng; Kartiasih, Fitri; A’mal , Ikhlasul (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Objective: This study aims to measure the extent of LPG usage inequality and to examine the factors influencing it across 13 provinces in Eastern Indonesia (KTI) over the period 2015–2023. Specifically, this study seeks to address two research questions: (1) To what extent does LPG usage inequality vary across provinces in Eastern Indonesia? and (2) What factors contribute to the occurrence of this inequality?Methods: This study uses panel data sourced from the National Socioeconomic Survey (Susenas) and official publications of BPS-Statistics Indonesia. LPG usage inequality is measured using the Gini Coefficient and the Lorenz Curve. The empirical model is analyzed using the Fixed Effect Model (FEM), which is then corrected with Feasible Generalized Least Squares–Seemingly Unrelated Regression (FGLS-SUR) to address heteroskedasticity and cross-sectional unit correlation issues.Findings: The research findings reveal that five provinces (East Nusa Tenggara, Maluku, North Maluku, Papua, and West Papua) experience very high disparities in LPG usage, primarily influenced by limited access and high LPG prices. Empirically, it was found that per capita income and education significantly reduce inequality, while an increase in LPG prices significantly increases inequality.Originality/Value: This research makes a novel contribution by focusing on LPG usage inequality across the provinces of Eastern Indonesia. The use of panel data analyzed through the FGLS-SUR method enables a more robust and precise identification of the determinants of inequality.Practical/Policy implication: The government should enhance the equity of energy distribution infrastructure, ensure price stability, and promote energy literacy as part of a just clean energy transition. Furthermore, improving educational attainment and strengthening micro, small, and medium enterprises (MSMEs) are essential to increasing public awareness, raising income levels, and stimulating regional economic development.